Prevalence of SLCO1B1 single nucleotide variations, and their association with statin intolerance in hypercholesterolaemic patients in Gauteng, South Africa - Soma, Prashilla (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 2020.